ANALISIS PENGARUH PDRB, SUKU BUNGA, TINGKAT INFLASI DAN KURS VALUTA ASING TERHADAP SIMPANAN MASYARAKAT PADA BANK UMUM DI KALIMANTAN BARAT - B61110034, YENNY HENDRA (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This research intent to know PDRB'S influence, rate of interest, inflation rate and foreign currency rate to society trove (DPK) on public banks at West Kalimantan. Data type that is utilized as time series's data, taken from by Statistical Write-up Data of Bank Indonesia, namely of Write-up Quarterly up to 8 years, of year 2004 2011, with data amount 32 moons. Analisis's tool that is utilized is analisis correlation and Multiple Regression, with OLS'S method, and Classical Assumsi Analisis. The Result observationaling to point out that: 1 ) PDRB (X1) having positive influence to DPK, pointed out by X1's regression coefficient as big as 3.063. 2) Kurs of Dollar Rate point (X2) having positive influence to DPK, with X2's regression coefficient as big as 0.201. 3) Inflation Rates (X3) having positive influence to DPK, with X3's regression coefficient as big as 0.001. 4) Depositos Rate Zooms (X4) having negative influence to DPK, with regression coefficient as big as 0.002. Its mean each depositos rate ascension as big as 1% therefore society trove amount (Y ) experience decrease as big as 0.002 percent. The result count of simultan correlation, known by determinant coefficient point (R 2 ) = 0,958. Its mean as a whole variation which happens on independent variable (PDRB, Rate Of Interest zoom, Inflation rate) word or regarding or available simultan's relationship to dependen's variable (DPK) as big as 96%, meanwhile, its rest (4%) worded by other variable. Meanwhile of yielding signifikansi's quiz partial, known just PDRB that influential signifikan to DPK, on trusty zoom 95%(? 5%). Its mean just PDRB that significant for developing to foot up DPK on public banks at Time former Western. Meanwhile of yielding signifikansi simultan's quiz (Quiz f) conclude that variable fourth free (rDeposito, rTabungan, Rate, PDRB, Inflation) influential together signifikan to Dependent Variable (DPK). Key word : DPK, PDRB, Kurs Valuta Asing, Inflasi, Suku Bunga